Quality of Gália 'DRG3228' melon fruits stored under refrigeration and application of chitosan and essential oils coatings (Research, Society and Development, 2022)
The use of coatings with chitosan and essential oils is being encouraged in fruit growing because they are widely found in nature, have low cost, reduce the environmental impacts associated with agrochemicals, extend post-harvest shelf life and improve their quality attributes. The objective was to evaluate the postharvest quality of melon type Gália 'DRG3228' stored under refrigeration and with application of chitosan and essential oils coatings. Fruits, maturation stage 2, were purchased at the “packing house” of Empresa Terra Santa, Quixeré-CE, washed with chlorinated water (150 ppm), sprayed with asparacetic (1:400 L of water), dried in fans and selected for division of the experimental groups into Control, Fungicide (company standard treatment with Imazalil 1ml.L-1), PP 25%, PP 50%, PP 75% (FToly Protect Prap Coating) and P 25%, P 50%, P 75 % (FTPoly Protect Coating). After drying, they were stored for 28 days in a cold chamber at 6 ± 1ºC, at 90 ± 1% relative humidity, and analyzed at seven-day intervals to determine the parameters of pulp firmness and soluble solids. There was no interaction between the factors studied and no significance between treatments. Firmness remained with constant averages until 14 days after harvest (DAC) (29.84 N), reducing 12.6% at 21 DAC (26.50 N). Soluble solids showed a significant difference from 14 DAC, from 13.96°Brix to 15.39°Brix. At the end of storage (28 DAC), the melons were at the minimum standards for acceptance in the foreign market, although they did not demonstrate significance between the coatings studied.